Sequential activation of microglia and astrocyte cytokine expression precedes increased iba‐1 or GFAP immunoreactivity following systemic immune challenge. Issue 2 (15th October 2015) - Norden, Diana M.; Trojanowski, Paige J.; Villanueva, Emmanuel; Navarro, Elisa; Godbout, Jonathan P.
Abstract : Activation of the peripheral immune system elicits a coordinated response from the central nervous system. Key to this immune to brain communication is that glia, microglia, and astrocytes, interpret and propagate inflammatory signals in the brain that influence physiological and behavioral responses. One issue in glial biology is that morphological analysis alone is used to report on glial activation state. Therefore, our objective was to compare behavioral responses after in vivo immune (lipopolysaccharide, LPS) challenge to glial specific mRNA and morphological profiles. Here, LPS challenge induced an immediate but transient sickness response with decreased locomotion and social interaction. Corresponding with active sickness behavior (2–12 h), inflammatory cytokine mRNA expression was elevated in enriched microglia and astrocytes. Although proinflammatory cytokine expression in microglia peaked 2‐4 h after LPS, astrocyte cytokine, and chemokine induction was delayed and peaked at 12 h. Morphological alterations in microglia (Iba‐1 + ) and astrocytes (GFAP + ), however, were undetected during this 2–12 h timeframe. Increased Iba‐1 immunoreactivity and de‐ramified microglia were evident 24 and 48 h after LPS but corresponded to the resolution phase of activation. Morphological alterations in astrocytes were undetected after LPS. Additionally, glial cytokine expression did not correlate with morphology after four repeated LPS injections. In fact, repeated LPS challenge was associated with immune and behavioral tolerance and a less inflammatory microglial profile compared with acute LPS challenge. Overall, induction of glial cytokine expression was sequential, aligned with active sickness behavior, and preceded increased Iba‐1 or GFAP immunoreactivity after LPS challenge. GLIA 2016;64:300–316 Main points: Glial induction of cytokines was sequential, aligned with active sickness behavior, and preceded increased Iba1 or GFAP immunoreactivity after LPS challenge. Microglial Iba1 or astrocytic GFAP immunoreactivity are unreliable indicators of activation.